Use of digital marketing as a learning platform and enhance operation of UpoharBD.com - Anila, Noorjahan (BRAC Univeristy, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.